Bifidobacterium animalis F1-7 in combination with konjac glucomannan improves constipation in mice via humoral transport. Issue 2 (4th January 2021) - Lu, Youyou; Yu, Zhuang; Zhang, Zhe; Liang, Xi; Gong, Pimin; Yi, Huaxi; Yang, Liuqing; Liu, Tongjie; Shi, Hanping; Zhang, Lanwei
Abstract : Bifidobacterium animalis F1-7 in combination with konjac glucomannan promoted the metabolism of tryptophan and short-chain fatty acids, regulated humoral transport and improved constipation. Abstract : Probiotics and natural products can promote humoral transport and effectively relieve intestinal motility. This study investigated the effects of probiotics in combination with konjac glucomannan (KGM) and an aqueous extract of Prunus persica on constipation. The growth promotion effect of these natural products on probiotics was investigated using co-culture in vitro . The combined effect of probiotics and natural products on constipation was observed in mice. The tryptophan, tryptamine and short-chain fatty acid levels were determined using enzyme-linked immunosorbent assay, reverse-phase high-performance liquid chromatography, and gas chromatography. The key genes and proteins involved in humoral transport were identified using real-time polymerase chain reaction, western blotting and fluorescence immunoassay. KGM promoted the growth of Bifidobacterium animalis F1-7 in vitro, and a mixture of KGM and B. animalis F1-7 effectively promoted defaecation in mice, increased the faecal water content, shortened the defaecation time and improved the gastrointestinal transit rate. In mice, the KGM + F1-7 mixture reduced the tryptophan level and increased the levels of tryptamine, acetic acid, propionic acid, butyric acid and valeric acid. In addition, the KGM + F1-7 mixture effectively increased the mRNA level of 5-HT4 -G-protein-coupled receptors (5-HT4 GPCR)/mucins-2 (MUC-2) and reduced the level of aquaporins (AQP3 ); furthermore, it upregulated the protein level of 5-HT4 GPCR/MUC-2 and downregulated the protein level of AQP3 . These findings indicated that the KGM + F1-7 mixture effectively improved intestinal motility and alleviated constipation through humoral transport-related pathways.